Evaluation of colonization by multiresistant bacteria in patients admitted via central regulation of the state in a philanthropic hospital in Salvador, Bahia - Monique Lírio; Tuanny Andrade; Ana Verena Mendes; Maria Goreth Barberino (Universidade de Santa Cruz do Sul, 2019)
Background and objectives: Health Care Related Infections (IRAS) are considered a public health problem whose control can minimize patients' morbidity and mortality. The early institution of contact isolation for patients possibly colonized by multiresistant (MR) microorganisms can reduce their spread in cases of IRAS and hospital costs. This study aimed to evaluate the frequency and impact of positive surveillance cultures with multiresistant (MR) microorganisms following an outbreak of vancomycin resistant Enterococcus spp. (VRE). Methods: Surveillance cultures collection routines were implemented since April / 14 for patients referred from other health to a philanthropic hospital in Salvador - Bahia via state and municipal referral center. Results: A total of 663 patients were evaluated in the period from December / 14 to December / 15, and 42 of them had a positive surveillance culture for gram positive and negative MR microorganisms. After the routine implementation of surveillance cultures, no outbreaks were detected in our unit. Conclusion: Despite the high cost, the study showed that routine surveillance cultures are an important tool in preventing MR dissemination.